Learning lessons in sepsis from the children - Steven Timmermans; Claude Libert (Molecular Systems Biology)
Abstract Sepsis research has had relatively limited therapeutic success so far. In their recent study, Kobzik and colleagues (Joachim et al, 2018) identify novel drug‐sensitive pathways in sepsis, derived exclusively from patient data. Their strategy is based on the analysis of a naturally sepsis‐resistant population (pre‐puberty children) and on the implementation of a novel‐rich Pathway Drug Network, constructed from human gene expression data enriched in drug–pathway–gene clusters.